Tribology of natural fiber polymer composites - Chand, Navin; Fahim, Mohammed (Woodhead Publishing series in composites science and engineering., 2020)
Tribology of Natural Fiber Polymer Composites, Second Edition, covers the availability and processing of natural fiber polymer composites and their structural, thermal, mechanical and tribological properties and performance. Environmental concerns are driving demand for biodegradable materials such as plant-based, natural fiber-reinforced polymer composites. These composites are fast replacing conventional materials in many industrial applications, especially in automobiles, where tribology (friction, lubrication and wear) is an important aspect.